Association between blood lipid profile and urolithiasis: A systematic review and meta‐analysis of observational studies. (27th August 2018) - Besiroglu, Huseyin; Ozbek, Emin
Abstract : The objective of this study was to pool individual studies regarding the association of blood lipid profiles with urolithiasis to carry out a systematic review and meta‐analysis. We searched MEDLINE, PubMed, Embase and Cochrane Library to identify the relevant studies up to November 2017. Studies that met all inclusion criteria were chosen, and a pooled analysis of the odds ratio between urolithiasis and dyslipidemia traits was calculated. A total of 11 observational studies (seven cross‐sectional, three cohort, one case–control) with a total of 282 479 participants were examined. The overall pooled analysis of eight studies showed that high triglyceride was associated with increased estimated risk of urolithiasis (odds ratio 1.287, 95% CI 1.073–1.544; P = 0.007). Estimates of the total effect size were consistent in the sensitivity analysis. No evidence of publication bias was detected. The overall pooled analysis of nine studies showed low high‐density lipoprotein was weakly associated with increased estimated risk of urolithiasis (odds ratio 1.171, 95% CI 1.010–1.358; P = 0.032). The sensitivity analysis showed conflicting results. No evidence of publication bias was detected. Three studies on the association between any dyslipidemia traits and urolithiasis showed a significant association (odds ratio 1.309, 95% CI 1.202–1.425; P < 0.001). The present meta‐analysis showed that patients with higher triglyceride and lower high‐density lipoprotein had an increased estimated risk of urolithiasis. A triglyceride–urolithiasis association was found to be more coherent and consistent compared with the high‐density lipoprotein–urolithiasis association. Although somewhat contradictory results have been found, the meta‐analysis is encouraging for evaluating urolithiasis as a systemic disorder. Further well‐designed prospective randomized controlled or cohort studies are necessary to better elucidate the causal association of dyslipidemia and urolithiasis.